THE EFFECT OF EXPERIMENTAL METHODS SUPPORTED AS REAL OBJECT MEDIA ON THE ABILITY OF IDENTIFYING GREEN PLANT MAKES FOOD STUDENTS OF FIFTH-GRADES SDN GUNUNG BOROK - Ernawati Ernawati; Nila Wahyu Mayaning Ati (Renjana Pendidikan Dasar, 2023)
This research is based on the observations and experiences of researchers, that science learning in elementary schools still dominates the role of the teacher who provides learning using the lecture method in each lesson and there is no learning media. These conditions make the learning atmosphere tend to be monotonous and boring, resulting in low student interest in learning. The aims of this study were (1) to find out the ability to identify how green plants make food taught by the experimental method without the help of real object media in fifth-grades students at SDN Gunung Borok (2) to find out the ability to identify green plants to make food taught by the experimental method assisted by real object media in fifth-grades students at SDN Gunung Borok (3) To determine the effect of the experimental method assisted by real object media on the ability to identify how green plants make food in fifth-grades SDN Gunung Borok. This study used a quantitative research approach with the research technique Quasi Experimental Design type Nonequivalent Control Group Design. The research subjects were 45 students of fifth-grades SDN Gunung Borok consisting of 23 students from fifth-grades-A as the experimental class who were treated using experimental methods supported by real object media and fifth-grades-B as many as 22 students as the control class only used the experimental method without the support of real object media. The conclusions from the results of this study were (1) The ability to identify how to make green plant food taught by experimental methods without the support of real object media obtained an average score of ≥ KKM, namely 77, this value can be seen from the posttest value data obtained by fifth grade students of SDN Gunung Borok (2) The ability to identify how green plants make food which is taught using experimental methods supported by real object media obtains a score above the KKM, namely 82, this value can be seen from the value of the posttest data obtained by fifth-grades students at SDN Gunung Borok (3) There is an influence An experimental method supported by real object media on the ability to identify how green plants make food in fifth-grades SDN Gunung Borok with a Sig. (2-tailed) 0.000 <0.005 thus Ho is rejected and Ha is accepted